Digital government at work : a social informatics perspective - McLoughlin, Ian, 1956- (Oxford University Press, 2013)
Drawing upon extensive research from inside live projects, this book examines the use of digital technologies to provide more joined-up public services, and combines cross-disciplinary insights to provide a new social informatics perspective on digital government.